Reducing costs and waste through analysis of statistical data in precision agriculture - Bonani, Jener Augusto; Nunes, Deivid Marques; Fernandes, Nilson José (Brazilian Journal of Production Engineering, 2024)
This study aims to analyze soil fertility using precision agriculture and demonstrate the possibility of reducing costs and quantities of applied inputs. The methodology of this study compares two soil analysis methods: one using the average in conventional agriculture and the other using precision agriculture. The results demonstrate the differences in decision-making between the methods. Using precision agriculture, a 19% saving in the costs of analyzed inputs was observed, in addition to an increase in production of 23.87% after only one year of applying the technique.
Keywords: Precision agriculture; Fertilizers; Inputs; Cost